The Relationship Between Human Resource Management Practices and Organizational Culture Towards Organizational Commitment: A Case at Tenaga Nasional Berhad - Raja Hang Tuah, Raja Iskandar (2011)
Common to most conceptualizations of commitment found in the literature is a link with turnover; employees who are strongly committed are those who are least likely to leave the organization. However, there are other factors that lead to the development of commitment and employee positive behaviour apart from the issue of remaining with the organization. This involved the psychological state as portrait in commitment that is link to the employee‘s attitude and it reflect the employee‘s relationship with the organization. Therefore, this study aims to prove whether there is a relationship and influence between human resource management practices (HRM) and organization culture towards organization commitment. Four dimensions of HRM practices namely, training and development; career development; salary and benefit; and performance appraisal; along with five dimensions of organization culture namely, job autonomy; external orientation; interdepartmental orientation; human resource orientation; and improvement orientation; on the influence and relationship towards Organization Commitment will be the focus of this study. This study will use the research instruments develop by the experts and original researcher already proven in terms of reliability and validity on human resource management practices ( Desimone, Werner and Harris, (2002); Hirsh et. al., (1995) and Maya, (1991); Kim, Price, Mueller and Watson, (1996); Hackman and Oldman, (1980); organizational culture (Van den Berg and Wilderom (2004) and Van der Post , De Coning and Smit (1997); and organizational commitment (Allen and Meyer, 1990). The data in this research was obtained through random sampling from the employees working at Institut Latihan Sultan Ahmad Shah (ILSAS). From a population of 240 employees at the institute, a total of 137 participated through the questionnaire that was distributed randomly. A total of 92 employees (67%) had duly completed and returned the forms. Mean analysis, standard deviation, Pearson correlation and linear regression were used to achieve the objectives of the study. Mean analysis shows that the level of agreement of the employees on the human resource practices and organizational culture is at the moderate level. The result of the Pearson correlation analysis shows that there is a significant and very high positive relationship between the human resource management practices and organizational culture towards organizational commitment. Whereas the linear regression analysis shows that the performance appraisal factor is the most influential factor (β = .675, p = .000) on the organizational commitment in Tenaga Nasional Berhad (TNB). TNB needs to relook at the HRM practices and HRM orientation to ensure that commitment to the organization can be improve and strengthen.